Effects of Pharmacologic and Nonpharmacologic Interventions on Insomnia Symptoms and Self-reported Sleep Quality in Women With Hot Flashes: A Pooled Analysis of Individual Participant Data From Four MsFLASH Trials. Issue 1 (6th January 2018) - Guthrie, Katherine A; Larson, Joseph C; Ensrud, Kristine E; Anderson, Garnet L; Carpenter, Janet S; Freeman, Ellen W; Joffe, Hadine; LaCroix, Andrea Z; Manson, JoAnn E; Morin, Charles M; Newton, Katherine M; Otte, Julie; et al.
Abstract: Study Objectives: The Menopause Strategies: Finding Lasting Answers for Symptoms and Health network conducted three randomized clinical trials (RCTs) testing six interventions treating vasomotor symptoms (VMS), and also collected self-reported sleep outcomes. A fourth RCT assessed an intervention for insomnia symptoms among women with VMS. We describe these seven interventions' effects relative to control in women with comparably severe insomnia symptoms and VMS. Methods: We analyzed pooled individual-level data from 546 peri- and postmenopausal women with Insomnia Severity Index (ISI) ≥ 12, and ≥14 bothersome VMS/week across the four RCTs. Interventions included the following: escitalopram 10–20 mg/day; yoga; aerobic exercise; 1.8 g/day omega-3 fatty acids; oral 17-beta-estradiol 0.5-mg/day; venlafaxine XR 75-mg/day; and cognitive behavioral therapy for insomnia (CBT-I). Outcome measures were ISI and Pittsburgh Sleep Quality Index (PSQI) over 8–12 weeks of treatment. Results: CBT-I produced the greatest reduction in ISI from baseline relative to control at −5.2 points (95% CI −7.0 to −3.4). Effects on ISI were similar for exercise at −2.1 and venlafaxine at −2.3 points. Comparably small decreases in ISI were observed with escitalopram, yoga, and estradiol. The largest reduction in PSQI from baseline was with CBT-I at −2.7 points (−3.9 to −1.5), although PSQI decreases of 1.2 to 1.6 points were significantly better than control with escitalopram, exercise, yoga, estradiol, and venlafaxine. Omega-3 supplements did not improve insomnia symptoms. Conclusions: This study's findings support current recommendations for CBT-I as a first line treatment in healthy midlife women with insomnia symptoms and moderately bothersome VMS.